Economic Analysis of Hydrogen Production and Storage Systems Utilizing Renewable Energy Sources - Ali Mohammed Elaibi (Journal of Mechanical Engineering, 2026)
By converting to an environmentally friendly energy system, water electrolysis technology based on renewable sources (like solar photovoltaic and wind power) has presented a sustainable route to carbon-neutral hydrogen generation. In this paper, we introduce a complete techno-economic characterization of renewable electric hydrogen production technologies within storage systems. Our review presents existing pricing profiles including electrolysis capital investment costs, renewable energy pricing systems, and operating parameters. We cover various storage forms (compressed gaseous hydrogen, cryogenic liquid hydrogen, geological formations) and three main electrolyzer technology stacks: alkaline electrolyzers (AEL), proton exchange membrane electrolyzers (PEM), and solid oxide electrolysis cells (SOEC). For these reasons, Levelized Cost of Hydrogen (LCOH) is considered the most significant economic indicator of these experiments. With data available that provides a glimpse of the potential cost reductions associated with scale-up of the manufacturing process, technological advancement, and decreasing costs associated with renewable energy, we sought to explore potential cost reductions regarding cost of this process. The total cost of producing low-carbon hydrogen is currently estimated at between $4 and $8 per kilogram, but it is projected to drop to $2 per kilogram by 2040, which is expected to be comparable to the cost of producing hydrogen from fossil fuels. To ensure the success of this technology, it is essential to develop integrated plans that combine, a supportive policy framework and the use of new methods to increase the efficiency of electrolysis, while maintaining reasonable cost-effectiveness, Total costs of producing low-carbon hydrogen.